Developmental exposure to corn grown on Lake Erie dredged material: a preliminary analysis - Flanigan, Kaylyn A. S.; Czuba, Madelyn I.; Riesgo, Victoria R.; Rúa, Megan A.; Stevenson, Louise M.; Willing, Jari (Frontiers in Behavioral Neuroscience, 2023)
While corn is considered to be a healthy food option, common agricultural practices, such as the application of soil amendments might be introducing contaminants of concern (COC) into corn plants. The use of dredged material, which contain contaminants such as heavy metals, polychlorinated biphenyls and polycyclic aromatic hydrocarbons, as a soil amendment is increasing. Contaminants from these amendments can accumulate in corn kernels harvested from plants grown on these sediments and potentially biomagnify in organisms that consume them. The extent to which secondary exposure to such contaminants in corn affect the mammalian central nervous system has been virtually unexplored. Here, we examine the effects of exposure to corn grown in dredge amended soil or a commercially available feed corn on behavior and hippocampal volume in male and female rats. Perinatal, but not adult, exposure to dredge-amended corn altered behavior in the open-field and object recognition tasks in adulthood. Additionally, dredge-amended corn led to a reduction in hippocampal volume in male but not female adult rats. These results suggest that dredge-amended crops and/or commercially available feed corn may be exposing animals to COC that can alter neurodevelopment in a sex-specific manner, and suggest that more research is needed to determine the potential consequences of certain soil amendments.